The role of artificial intelligence in modern cybersecurity - Veronika Koliusheva; Olena Hurska; Гурська Олена (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In the digital age, cybersecurity has become one of the most critical domains influencing the stability of financial systems, government operations, and daily routines. Our reliance on connected devices, online services, and data-driven systems has made us more open to cyberattacks, which are growing in number and getting more complex. Old ways of protecting data are not enough to handle the speed, extent, and sophistication of threats we see today. This challenge underlines the relevance of integrating artificial intelligence (AI) into cybersecurity systems. AI refers to the application of intelligent algorithms and machine learning techniques that allow systems to analyze massive datasets, detect anomalies, and adapt dynamically to emerging threats. The novelty of AI lies in its ability to learn autonomously, making cybersecurity tools more proactive, adaptive, and efficient. The objective of this research is to examine how AI transforms modern cybersecurity through automation, data-driven decision-making, and predictive analytics, while also evaluating the potential risks and ethical challenges associated with its implementation. AI helps cybersecurity by automating tasks and constantly studying data to handle huge amounts of info and react to threats as they happen. Things like machine learning and neural networks help AI systems learn from what they see and get better over time. These tools are getting better at doing what traditional tools, like firewalls and antivirus tools do. They improve how well systems can adapt and spot dangers. AI systems can study how data moves across networks, find suspicious patterns, and take action even before people notice something's wrong. These systems guard data across different cloud setups, find odd actions, and tell cybersecurity teams about possible breaches. By joining automatic threat finding with human knowledge, we can cut down the time it takes to find and fix attacks, which makes everything more secure.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: cybersecurity; artificial intelligence; neural networks